2018
DOI: 10.3390/nu10101398
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Trimethylamine N-Oxide (TMAO) in Disease: Potential Biomarker or New Therapeutic Target

Abstract: Trimethylamine N-oxide (TMAO) is a molecule generated from choline, betaine, and carnitine via gut microbial metabolism. The plasma level of TMAO is determined by several factors including diet, gut microbial flora, drug administration and liver flavin monooxygenase activity. In humans, recent clinical studies evidence a positive correlation between elevated plasma levels of TMAO and an increased risk for major adverse cardiovascular events. A direct correlation between increased TMAO levels and neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
375
2
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(399 citation statements)
references
References 103 publications
(169 reference statements)
8
375
2
14
Order By: Relevance
“…Trimethylamine N-oxide is an important pro-atherogenic metabolite produced by gut microbiota, and gut microbial enzymes were involved in the formation of its precursor trimethylamine (TMA) (Wang et al, 2011;Koeth et al, 2013). Previous studies confirmed that choline TMA lyase (K20038), betaine reductase (K21578, K21579) and L-carnitine CoAtransferase (K08298) are the main TMA-lyases involved in TMA production (Fennema et al, 2016;Zeisel and Warrier, 2017;Janeiro et al, 2018). Results at the KO level exhibited decreased abundance of betaine reductase (K21578, K21579) in both the high and low dose BBR groups compared to the model group, and was especially significantly in the low dose group (all p < 0.01, Figures 9A,B).…”
Section: Functional Alterations In Gut Microbiota Induced By Bbrmentioning
confidence: 99%
“…Trimethylamine N-oxide is an important pro-atherogenic metabolite produced by gut microbiota, and gut microbial enzymes were involved in the formation of its precursor trimethylamine (TMA) (Wang et al, 2011;Koeth et al, 2013). Previous studies confirmed that choline TMA lyase (K20038), betaine reductase (K21578, K21579) and L-carnitine CoAtransferase (K08298) are the main TMA-lyases involved in TMA production (Fennema et al, 2016;Zeisel and Warrier, 2017;Janeiro et al, 2018). Results at the KO level exhibited decreased abundance of betaine reductase (K21578, K21579) in both the high and low dose BBR groups compared to the model group, and was especially significantly in the low dose group (all p < 0.01, Figures 9A,B).…”
Section: Functional Alterations In Gut Microbiota Induced By Bbrmentioning
confidence: 99%
“…As an example, the gut microbiome product TMAO has been considered a shared risk factor between numerous diseases, such as IR, cancer, Alzheimer's disease (AD) and schizophrenia, among others [238,239]. Clinical studies have described that higher circulating levels of TMAO are correlated with a higher inflammatory response (↑ C-reactive protein, ↑ TNF-α, ↑ IL-6) [240]. Moreover, it is related to the synthesis of N-Nitroso compounds, which are involved in epigenetic alterations and DNA-damage that can lead to the induction of cancer [241].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Importantly, SCFAs, particularly butyric and acetic acid, which derive mainly from the bacterial fermentation of fiber, are considered to promote cardiovascular health. In contrast, trimethylamine-N-oxide (TMAO), a metabolite produced by the gut microbiota from choline, betaine, and carnitine, which are abundant in meat, eggs, and fish, is associated with excess risk of heart disease [134].…”
Section: Microbiotamentioning
confidence: 99%